The effects of implementing Quality Management Systems (QMS) on the performance of parastatals in Zimbabwe: the case of Zimbabwe Power Company Munyati - Njobo, Learnmore (Midlands State University, 2017)
The key calling of any parastatal in Zimbabwe is to pursue public interests, parastatals are tasked with the duty to provide services that benefit the public in the long-term. In the 21st century Zimbabwean parastatals have been the country ‘s bane, draining the fiscus while failing to perform the functions for which there were set out to do.in 2013 the Auditor General Mildred Chiri outlined that parastatals operate in red, continuously bleeding the fiscus and in most instances failing to adequately provide the services which they are set for. To improve public backing and confidence, parastatals are now under the commitment to fasten their belts to sustain the fundamentals of excellent pursuit for public interest. Alongside ZIMCODE which advocates for good corporate governance associated with a set of systems, principles and processes by which parastatals should be governed, a number of parastatals also adopted Quality Management Systems, hereinafter QMS .Standards Association Of Zimbabwe (2013) posits that the adoption of Quality Management Systems is a strategic decision of an organisation and is influenced by the need to demonstrate its ability to consistently provide product and services that meets customer and applicable statutory and regulatory requirements, the entity will also strive to satisfy customers by way of properly implementing the principles of QMS which include continual improvement which guarantees customer satisfaction. The researcher made use of Zimbabwe Power Company Munyati Power Station as a case study because it is one of the parastatals which was certified to have adopted and implementing QMS. According to the 2015 annual report of Zimbabwe Power Company Munyati Power Station, the organisation was endorsed by Standards Association Zimbabwe to be using QMS requirements in November 2014 and the motive behind was to improve performance by enhancing customer satisfaction and better service delivery. Nonetheless there is no much improvement to write home about in the Zimbabwean parastatals despite adopting Quality Management System thus this study seeks to unravel why the intended benefits of Quality Management Systems are not being realised. The researcher used both quantitative and qualitative methods of data collection as he used structured questionnaires and unstructured interview questions to obtain the data which was going to bring about the objectives of the study research such as exploring the elements and applicability of Quality Management Systems in Zimbabwean parastatals, analysing the factors for the implementation of Quality Management, to assess the factors hindering the implementation of Quality Management Systems and to proffer recommendations for the enhancing the implementation of Quality Management Systems in Zimbabwean Parastatals. The research findings reviewed and concluded that Quality Management Systems is applicable in Zimbabwean parastatals and can enhance the performance of parastatals if properly implemented, the study also unearthed that the intended benefits of Quality Management Systems are not being fully realised in Zimbabwean parastatals mainly because of bureaucratic interventions and obsolete machinery. The study reviewed that there are other measures that must be put in place to reinforce any hopes of fully realising the intendent benefits of Quality Management Systems such as adopting New Public Management, privatisation and others. The Zimbabwean parastatals are recommended to adopt New Public Management which does not allow the interference of bureaucratic people like ministers and politicians in the day to day running of parastatals. There are also other recommendations such as privatising some of the parastatals.